Densely Packed Fiber Electrodes Composed of Liquid Crystalline MXenes for High‐Areal‐Density Supercapacitors. Issue 4 (17th February 2023) - Kim, Joonhui; Kim, Seulgi; Yuk, Seoyeon; Hwang, Hyewon; Song, Sung Ho; Byun, Segi; Lee, Dongju
Abstract : Because electrode structure is a crucial determinant of supercapacitor performance, there are multiple studies of supercapacitor electrodes with various structures. Here, experimental observations of the diameter‐dependent supercapacitor performance of a liquid crystalline (LC)‐assisted MXene fiber‐based electrode produced through a wet‐spinning process is reported. It is shown that Ti3 C2 T x nanosheets are highly dispersed in water and do not form aggregates or undergo phase separation. MXene dispersion exhibits the typical shear thinning behavior of liquid crystals above the critical mass fraction. Various MXene fibers derived from needles of different diameters can be produced using one method. LC‐assisted MXene fibers are characterized by a high electrical conductivity of up to 2012.27 S cm −1 . Furthermore, the optimized MXene fiber‐based device has an areal capacitance of up to ≈6.82 F cm −2, indicating the utility of LC‐assisted MXene fibers in fiber‐shaped supercapacitor devices. The synthetic method has considerable advantages for applications in high‐performance supercapacitors with both stable device operation and high areal capacitance. Abstract : Liquid crystalline‐assisted Ti3 C2 T x MXene fibers with different diameters are successfully produced by the wet‐spinning process. This approach provides well‐aligned MXene sheets inside the fibers with a high areal packing density and MXene fiber‐based electrodes exhibit improved areal capacitance and rate performance.